Correlative light-electron fractography of interlaminar fracture in a carbon-epoxy composite - Hein, Luis Rogerio de O. [UNESP]; Campos, Kamila A. de [UNESP] (Microscopy and Microanalysis, 2015)
This work evaluates the use of light microscopes (LMs) as a tool for interlaminar fracture of polymer composite investigation with the aid of correlative fractography. Correlative fractography consists of an association of the extended depth of focus (EDF) method, based on reflected LM, with scanning electron microscopy (SEM) to evaluate interlaminar fractures. The use of these combined techniques is exemplified here for the mode I fracture of carbon-epoxy plain-weave reinforced composite. The EDF-LM is a digital image-processing method that consists of the extraction of in-focus pixels for each x-y coordinate in an image from a stack of Z-ordered digital pictures from an LM, resulting in a fully focused picture and a height elevation map for each stack. SEM is the most used tool for the identification of fracture mechanisms in a qualitative approach, with the combined advantages of a large focus depth and fine lateral resolution. However, LMs, with EDF software, may bypass the restriction on focus depth and present enough lateral resolution at low magnification. Finally, correlative fractography can provide the general comprehension of fracture processes, with the benefits of the association of different resolution scales and contrast modes.
Keywords: Composites; Correlative microscopy; Electron microscopy; Fractography; Light microscopy